Factors associated with successful fasting among type 2 diabetic mellitus patients during Ramadan: a retrospective recall study - Leow, Shing Ni; Tong, Seng Fah (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
Among diabetic patients, fasting is associated with increased risk of ketoacidosis, hypoglycaemia and dehydration. Previous randomised controlled trials and prospective studies have shown that intensive pre-Ramadan education on fasting is able to help patients fast successfully during Ramadan. At the same time, observational studies show that many diabetic patients are still able to fast successfully throughout Ramadan despite deficiencies in knowledge about fasting practices. We conducted a retrospective recall study in Klinik Kesihatan Jalan Perak, Penang to determine the factors associated with successful fasting. Patients were selected using convenience sampling. Successful fasting was defined as a patient fasted as intended, and not having to break-fast due to hypo/ hyperglycaemia symptoms or hospitalization due to diabetic complications. Multiple logistic regression was used to determine independent factors associated with successful fasting. 113 patients were enrolled. 70.9% (n=80) of patients were able to fast successfully. Knowing the name of their diabetic medications were significantly associated with successful fasting (AOR=8.56, 95%CI: 2.04;35.8, p=0.003). Knowledge and fasting practices were not associated with successful fasting. We may identify patients who might not fast successfully by evaluating their understanding of their diabetic medications. They can then be targeted for further pre-Ramadan counselling. Nonetheless, an intensive pre-Ramadan counselling is still optimal if resources are available.